2015
DOI: 10.18632/oncotarget.4690
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Wnt/β-catenin signaling in driving epithelial ovarian cancer platinum resistance

Abstract: Resistance to platinum-based chemotherapy is the major barrier to treating epithelial ovarian cancer. To improve patient outcomes, it is critical to identify the underlying mechanisms that promote platinum resistance. Emerging evidence supports the concept that platinum-based therapies are able to eliminate the bulk of differentiated cancer cells, but are unable to eliminate cancer initiating cells (CIC). To date, the relevant pathways that regulate ovarian CICs remain elusive. Several correlative studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 46 publications
(54 reference statements)
7
159
0
Order By: Relevance
“…Our data using activators and inhibitors of Wnt signaling support an inverse correlation between Wnt activation and platinum sensitivity. Our data are consistent with reports suggesting inhibition of Wnt target genes after platinum therapy [38], but dissimilar to studies supporting Wnt inhibition as a modality or re-sensitizing OC to platinum [39]. The distinct cell models and experimental conditions (selection of platinum resistant tumors in vivo vs. in vitro , different doses of inhibitors) may account for the observed differences.…”
Section: Discussionsupporting
confidence: 88%
“…Our data using activators and inhibitors of Wnt signaling support an inverse correlation between Wnt activation and platinum sensitivity. Our data are consistent with reports suggesting inhibition of Wnt target genes after platinum therapy [38], but dissimilar to studies supporting Wnt inhibition as a modality or re-sensitizing OC to platinum [39]. The distinct cell models and experimental conditions (selection of platinum resistant tumors in vivo vs. in vitro , different doses of inhibitors) may account for the observed differences.…”
Section: Discussionsupporting
confidence: 88%
“…We evaluated two paired cell lines: the cisplatin sensitive A2780 cell line and its cisplatin resistant derivative CP70, together with the cisplatin sensitive OV81.2 cell line, which is a primary cell line derived from a high grade serous ovarian cancer patient. The cisplatin resistant derivative OV81.2-CP10 (referred to as CP10 henceforth) was derived by propagating OV81.2 cells in the presence of cisplatin for 10 passages thus selecting for resistant clones [24]. …”
Section: Resultsmentioning
confidence: 99%
“…This is often related to reduced platinum accumulation in ovarian cancer cells, linked to increased expression of multidrug resistance associated transporters [29]. In ovarian cancer, platinum resistance has also been associated with an increase in stem-like properties mediated by upregulated Wnt signaling [24] and differential expression of microRNAs such as miR-181a [30]. More recently several studies have highlighted the importance of altered glucose or fatty acid metabolism in mediating resistance to chemotherapy or targeted therapies [3138].…”
Section: Discussionmentioning
confidence: 99%
“…It's reported that there will be totally 21,290 new cases and 14,180 new deaths in United States in 2015 [1]. Epithelial ovarian cancer (EOC) accounts for 90% to 95% of all cases of ovarian cancer [2, 3]. However, the etiology of EOC is not well understood but is likely to involve both genetic and environmental factors [4].…”
Section: Introductionmentioning
confidence: 99%